ANALISIS PEMAHAMAN MASYARAKAT TERHADAP NISBAH PADA MUDHARABAH DI BANK BSI GATOT SUBROTO KOTA JAMBI - Raden Muhamad Royru; Ahmad Syahrizal; Sissah (ICONS: Islamic Economics Journal, 2025)
This study aims to analyze the public's understanding of the profit-sharing ratio (nisbah) in mudharabah at Bank Syariah Indonesia (BSI) Gatot Subroto, Jambi City. Using a qualitative approach, data were collected through interviews, observations, and documentation. Participants included bank customers and employees, providing insights into their understanding of the nisbah mechanism in mudharabah products. The results indicate that the public's understanding varies, with most customers recognizing the importance of nisbah as an indicator of profit sharing. However, there are still gaps in understanding the detailed mechanisms and calculations of nisbah. This research suggests the need for further education for the community on the technical aspects of mudharabah, enabling customers to make more informed and prudent decisions when choosing sharia financial products. The findings of this study are expected to contribute to enhancing financial literacy in the community.